FAMILY LAUXANIIDAE - Silva, Vera Cristina (Zootaxa, 2016)
An updated Catalogue of the Lauxaniidae of Colombia is presented. This acalyptratae family is poorly known in Colombia, with only 36 described species in 33 genera. This paper expands the distribution of 24 species to Colombia. At total, 63 species are reported here for Colombia.